The Effect of Social Support and Gender on Head of Family of Quality of Life - Talha Dangkua (IJEEM - Indonesian Journal of Environmental Education and Management, 2018)
The research is aim at finding out the information about the effect of social support and gender on quality of life (QoL). An expost facto method has been applied by involving n=56 of head of family in distric of Pohuwato, Gorontalo. Design of this reaserch was 2 x 2 faktorial design. There were three instruments developed, instrument for measuring quality of life which consist of 41 items, social support around 30 items which all instrument are valid and reliable. Data has been Analyzed by applying two way ANOVA. The research result that there is Quality of life (QoL) difference between head of family with strong social support and weak social support. There are also differences of quality of life (QoL) between men and women of head of family. It is found that there is a significant interaction effect between social support and gender on quality of life (QoL). It could be concluded that if quality of life (QoL) could be improved, social support could be enhanced by considering head of family gender. It doesn’t guarantee that the more strong of head of family social support would be able to improve quality of life (QoL), however it depends on their gender as well